Shear band fracture in metallic glass: Hot or cold?. (15th March 2019) - Qu, R.T.; Wang, S.G.; Li, G.J.; Wang, R.F.; Wang, X.D.; Wu, S.J.; Zhang, Z.F.
Abstract: Usually, the fracture of metallic glass accompanies with huge heat release, resulting in the well-known localized melting and formation of vein patterns. In this work, using X-ray tomography and tin-coating methods, we found that the shear fracture of metallic glass under compression can be also "cold" if slowing down the fracture process. The results clarify that the melting phenomenon is not a necessary outcome of shear-band fracture, while the temperature-rise relies strongly on the energy release per unit shearing time, even in the fracture process. Graphical abstract: Unlabelled Image